Morphological and physiological characteristics of seedlings of different eastern beech (Fagus orientalis Lipsky.) populations - Gulseven, Orhan; Ayan, Sezgin; Özel, Halil Barış; Yer, Esra Nurten (Turkish Journal of Forestry, 2019)
The ecological conditions of nurseries can have an impact on both morphological and physiological characteristics of seedlings and may affect their development. Furthermore, the genetic characteristics of the populations adapted to the conditions of the growing environment, also influence the development of the seedlings. In this study, seeds collected from different districts of the natural distribution area of Eastern beech (Fagus orientalis Lipsky.) were sown under the same ecological conditions. Morphological and physiological characteristics of the seedlings belonging to different populations under the same ecological conditions were compared. In this study; Seeds from Bursa-İnegöl, Balıkesir-Dursunbey, Sakarya-Akyazı, Kastamonu-Çatalzeytin, Zonguldak-Devrek-Tefen, Zonguldak-Devrek-Akçasu and Bartın-Yenihan populations were supplied and grown in Zonguldak Gökçebey State Forestry Nursery. At the end of the 2nd vegetation period; physiological [chlorophyll a, chlorophyll b, total chlorophyll, relative humidity percentage on leaf (NNİ%) and cumulative transpiration (S)] and morphological characteristics [seedling height (FB), diameter of root collar (KBÇ), number of seedling branches (FDS), the fresh weight of the shoot and root (GTA, KTA), the total fresh weight of the seedlings (TFTA), the dry weight of the shoot and root (GKA, KKA), the total dry weight of the seedlings (TFKA), dry root percentage (%KKök), shoot-root ratio (KI), sturdiness index (GI) and Dickson quality index (DKI)] of 2+0 aged bare root seedlings were determined. As a result; the population factor affected a significant variation in all morphological characters except the shoot-root ratio (KI) and the sturdiness index (GI). In addition, it was determined that the population factor caused significant difference on the physiological properties of total chlorophyll amount and NNİ% of seedlings. The seedlings belonging to Zonguldak-Devrek-Akçasu and Zonguldak-Devrek-Tefen populations had the highest values in terms of both morphological and physiological characteristics. The most important issue that attracts attention in the research; It is stated that the seedlings obtained from the populations closest to the nursery ecology have the highest seedling values.
Keywords: oriental beech; seedling characters; seedling quality; Mühendislik; population; Doğu Kayını; Fidan kalitesi; Populasyon; Sınıflandırma standartları; Fidan karakterleri; sınıflandırma standartları; Forestry; SD1-669.5; quality standarts; fidan kalitesi; doğu kayını; Engineering; populasyon; fidan karakterleri; Oriental beech; Seedling quality; Population; Quality standarts; Seedling characters; 2. Zero hunger; 15. Life on land